Le cadrage religieux de la mobilisation « anti-genre » : une étude micro-événementielle du Family Day - Massimo Prearo (Genre, Sexualité et Société)
This article proposes an analysis of the uses of religious discourse in the "anti-gender" mobilization processes in Italy. Based on a micro-analytic observation of the Family Day demonstration in Rome (June 2015), the article examines, on the one hand, the theoretical-political framework of the "anti-gender" cause; and, on the other hand, the strategic use of a Catholic religious framework to strengthen the adhesion to the cause. I observe the modalities of participation in the demonstration and the mediation of a charismatic leader in order to build a repoliticized Catholic identity. I also analyze the process of construction of the fieldwork by revealing how my questionings and misunderstandings as a researcher in situ make visible what a macroscopic scale centered on structural or systemic models fail to grasp.